A Study on A New Class of q-Bernoulli, q-Euler and q-Genocchi Polynomials - Momenzadeh, Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This thesis is aimed to study a new class of Bernoulli, Euler and Genocchi polynomials in the means of quantum forms. To achieve this aim, we introduce a new class of q-exponential function and using properties of this function; we reach to the interesting formulae. The q-analogue of some familiar relations as an addition theorem for these polynomials is found. Explicit relations between these classes of polynomials are given. In addition, the new differential equations related to these polynomials are studied. Moreover, improved q-exponential function creates a new class of q-Bernoulli numbers and like the ordinary case, all the odd coefficient becomes zero and leads us to the relation of these numbers and q-trigonometric functions. At the end we introduce a unification form of q-exponential function. In this way all the properties of these kinds of polynomials investigated in a general case. We also focus on two important properties of q-exponential function that lead us to the symmetric form of q- Euler, q-Bernoulli and q-Genocchi numbers. These properties and the conditions of them are studied. Keywords: q-Exponential Function, q-Calculus, q-Polynomials, q-Bernoulli, q- Euler, q-Genocchi, q-Trigonometric Functions.

ÖZ: Bu tez kuantum formları uasıtası ile Bernoulli, Euler ve Gennochi polinomların yeni bir sınıfını incelemeyi amaçlamaktadır. Bu amaca ulaşmak için, q-üstel fonksiyonları ve bu fonksiyonların özellikleri kullanılarak yeni bir sınıf tanıtılmıştır.Bu polinomlar için bazı bilindik ilıskilerin q-uyarlamları ek teorem olarak bulunmuştur. Bu tür polinom sınıfları arasındaki kapalı ilişkiler verilmiştir. Ayrıca bu polinomlarla ilişkili yeni diferansiyel denklemler çalışılmıştır. Geliştirilmiş q-üstel fonksiyonlarnin yeni bir q-Bernoulli sayısı oluşturduğu da gösterilmiştir. Buna göre bilinen q-1 durumunda oldügu gibi tüm tek katsayların sıfır olarak q-üstel fonksiyonları, için birleşme formu, elde edilmiştir. Böylelıkle, bu tür polinomların tüm özellikleri genelleştirilmiştir. Ayrıca, q-Euler, q-Bernoulli ve q-Gennochi sayılaının simetri formlarını elde etmemızi sağloyon, iki önemli q-üstel fonksiyon özelliğine de odaklanılmıştır. Anahtar Kelimeler: q-Üstel Fonksiyonlar, q-Kalkülüs, q-Polinomlar, q-Bernoulli, q-Euler, q-Genocchi, q-Trigonometrik Fonksiyonla.
Doctor of Philosophy in Applied Mathematics and Computer Science. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2016. Supervisor: Prof. Dr. Nazim I. Mahmudov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Differential Equations; Mathematical Functions; Mathematical physics; q-Exponential Function; q-Calculus; q-Polynomials; q-Bernoulli; q-Euler; q-Genocchi; q-Trigonometric Functions